ANALYSIS OF THE LEVEL OF DIFFICULTY OF CLASS V PRIMARY SCHOOL STUDENTS IN WRITING SHORT STORIES IN THE SUBJECT OF ENGLISH - Ayu Komalasari; Aswadi Jaya; Mega Prasrihamni (Esteem Journal of English Education Study Programme, 2024)
This research aims to determine the factors that cause the level of difficulty in writing short stories in class V English at SD Negeri 06 Sungai Pinang and efforts to overcome them. The type of research used is qualitative descriptive research with the research object being a small scope which is the focus of the research. Based on the description of the results of research analysis carried out in class V of SD Negeri 06 Sungai Pinang, from the results of observations it is known that class V students of SD Negeri 06 Sungai Pinang are still relatively low in writing short stories. This is caused by internal and external factors of students. Efforts made to overcome students' difficulties in writing short stories are by providing additional hours for students who have difficulty writing.